2013
DOI: 10.1017/s000711451200520x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total homocysteine status of vegetarians compared with omnivores: a systematic review and meta-analysis

Abstract: There is strong evidence indicating that elevated plasma total homocysteine (tHcy) levels are a major independent biomarker and/or a contributor to chronic conditions, such as CVD. A deficiency of vitamin B 12 can elevate homocysteine. Vegetarians are a group of the population who are potentially at greater risk of vitamin B 12 deficiency than omnivores. This is the first systematic review and meta-analysis to appraise a range of studies that compared the homocysteine and vitamin B 12 levels of vegetarians and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 48 publications
4
76
0
4
Order By: Relevance
“…Overall, these have shown that a wellplanned vegetarian or vegan diet can supply all the nutrients required for good health (6) . However, some concern remains over the possibility of low intakes of some nutrients such as vitamin B 12 , vitamin D, calcium and n-3 fatty acids in poorly selected and/or unfortified vegetarian or vegan diets (7,8) ; in particular, vitamin B 12 status has been widely observed to be relatively low in vegetarians and especially in vegans, and this is associated with relatively high plasma homocysteine (9) . Many studies have assessed health-related factors such as BMI, plasma cholesterol concentrations and blood pressure in vegetarians, but relatively few studies have been of sufficient magnitude and duration to examine the long-term health of vegetarians and vegans.…”
mentioning
confidence: 99%
“…Overall, these have shown that a wellplanned vegetarian or vegan diet can supply all the nutrients required for good health (6) . However, some concern remains over the possibility of low intakes of some nutrients such as vitamin B 12 , vitamin D, calcium and n-3 fatty acids in poorly selected and/or unfortified vegetarian or vegan diets (7,8) ; in particular, vitamin B 12 status has been widely observed to be relatively low in vegetarians and especially in vegans, and this is associated with relatively high plasma homocysteine (9) . Many studies have assessed health-related factors such as BMI, plasma cholesterol concentrations and blood pressure in vegetarians, but relatively few studies have been of sufficient magnitude and duration to examine the long-term health of vegetarians and vegans.…”
mentioning
confidence: 99%
“…Since homocysteine (Hcy) metabolism is catalysed by enzymes requiring B vitamins as cofactors, tHcy can also be considered a marker for folate and cobalamin deficiency [3,4].…”
mentioning
confidence: 99%
“…Hyperhomocysteinemia is well established as an independent risk factor for coronary heart disease and arteriosclerosis. Studies have shown that coronary heart disease is linked to plasma Hcy levels, with a substantial risk occurring at > 10 μmol/L plasma Hcy; furthermore, each 5 μmol/L increase in plasma Hcy is associated with a 20% increased risk of coronary heart disease events [17]. The etiological factors for atherosclerosis raise conversion of methionine to Hcy thiolactone, which is the reactive cyclic internal lactone of Hcy, leading to a consequent thiolation reaction of amine-containing low-density lipoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that plasma tHcy levels correlate with the intake of animal source foods, the only natural abundant source of vitamin B 12 [17], while low intake of fruit and vegetables, natural folate sources, may be associated with inadequate folate intake [12, 25]. …”
Section: Discussionmentioning
confidence: 99%